Management and Sustainability Model in Diamond Route (Non-commercial Open Access) Scientific Journals of Universidad Nacional, Costa Rica: Translation to Portuguese - Mora-Campos, Andrea (2024)
Aim. Describe the construction stages of a structure that organizes the good practices derived from the design of a management and sustainability model for diamond scientific journals (non-commercial open access) at the National University, Costa Rica. Introduction. An assessment of the Latin American, Costa Rican, and institutional context is carried out in terms of policies on open knowledge of the last 20 years. The institutional route and the chronological record that shows the evolution of the editorial management of the journals since the creation of the first one, approximately 50 years ago, are described. Management model. The development of the scientific journal management model is detailed; it considers the conceptualization, the guiding principles, the work team, the support and advisory bodies, financial sustainability, and the monitoring and evaluation of journals. Results. The model’s innovation, adaptability, and alignment with international standards stand out; in addition to collaborative work, strategic planning, and institutional protection, which, mainly, leads to the creation of tangible products such as a regulation and a procedure manual, among others. Conclusions. The ability to adapt in the editorial management of scientific journals is crucial for scientific and social progress. This model promotes sustainability and editorial quality with emphasis on the diamond path, Open Science, and student inclusion, and its international impact is recognized in promoting science as a public good and in the resistance to models based on Article Processing Charges (APC). Recommendations. Are focused on the different sectors that manage scientific communication, highlighting the importance of promoting non-commercial open access, generating spaces to discuss the financial sustainability of open knowledge editorial management, and creating spaces for international cooperation. Finally, recognizing scientific communication as a public good must be accompanied by concrete actions that ensure adequate and stable resources that allow maintaining quality editorial management and promote ethical and transparent practices.